Experiencias de los beneficiarios erradicación del proyecto erradicación trabajo infantil (eti) del cantón La Joya de los Sachas, primer semestre 2023. - Castro Arias, Jenniffer Mishell (2024)
The present research addresses one of the most present social problems worldwide, “child labor”, for which the Project for the Eradication of Child Labor “ETI” of the La Joya de los Sachas canton was taken into account, to learn about the experiences of the boys, girls and adolescents who are part of the project, it is important to know that the ETI Project integrates children who are in situations of child labor with the purpose of eradicating this problem through various activities and, above all, guarantee compliance of the rights of children and adolescents. To achieve the stated objectives, quantitative methodology has been used, which will allow us to obtain data and describe the reality of the people involved, through the type of explanatory and descriptive research, taking into account the collection of data and surveys applied to each of them. children, this research requires knowing the work that the ETI project is carrying out on the children of the canton, to determine in what aspects it has benefited the minors based on the experiences lived throughout the process to which they have been included. Poverty, inequality and unemployment are some of the factors that lead minors to work situations in different areas such as agriculture, recycling, street vendors, among others, and as consequences there is school dropout, poor academic performance and children with disabilities. low self-esteem. Keywords: Child labor, poverty, school dropouts, unemployment, social problem.